Efektifitas Kombinasi Media dalam Penyisihan BOD dan TSS Limbah Cair Rumah Makan Menggunakan Constructed Wetland dengan Tanaman Cyperus Papyrus: The Effectiveness of Media Combination in BOD and TSS Removal of Restaurant Liquid Waste Using Constructed Wetland with Cyperus Papyrus Plants - Oktavia, Lily; Hidayat, Akhmad Danang Nur; Purnama, Agus Rachmad; Taqwanur, Taqwanur (Media Ilmiah Teknik Lingkungan (MITL), 2023)
The restaurant business can have an impact on increasing liquid waste which can contaminate the receiving water body. One of the treatment methods that can be applied as further treatment is a constructed wetland system with continuous flow. The aim of the research was to determine the amount of BOD and TSS removal and the effect of pH and temperature on the research. Preliminary tests conducted showed levels of BOD = 1,562 mg/L and TSS = 192 mg/L. The research reactor consisted of 3 units, filled with wastewater with a debit of 7 ml/minute and 5 Cyperus papyrus stems planted in a variety of planting media, the reactor containing clay growing media (R1), the reactor containing sand growing media (R2), and (R3). containing clay planting medium combined with sand media. The reactor used continuous flow for 4 days, starting with a 7-day acclimatization test. The parameters to be tested in this study are pH, temperature, BOD, and TSS. The results showed that constructed wetlands with Cyperus papyrus plants could remove the best BOD on day 1 in a reactor with clay media of 66%. In the constructed wetland test results with the Cyperus papyrus plant the best ability to remove TSS was achieved on day 2 in sand media (R2) which could remove TSS levels of 84.3%.